Update on combined immunotherapy for the treatment of advanced renal cell carcinoma - Georges Gebrael; Kamal Kant Sahu; Neeraj Agarwal; Benjamin L. Maughan (Taylor & Francis Group, 2023)
There has been substantial evolution in the treatment of metastatic renal cell carcinoma with notable changes in the first-line setting. Currently, doublet combination therapy with either two immune checkpoint inhibitors or a combination of an immune checkpoint and tyrosine kinase inhibitor is considered the standard of care. The doublet combination therapies have demonstrated significantly improved clinical outcomes. A recently conducted trial (COSMIC-313) showed superior efficacy with a triplet combination of cabozantinib, nivolumab, and ipilimumab when compared to a placebo, nivolumab, and ipilimumab but at the cost of additional toxicity. Many other combination treatments, such as pembrolizumab plus lenvatinib plus belzutifan (NCT04976634), are being investigated, possibly leading to more options in the first-line setting in the future.